2023
DOI: 10.1111/ffe.14051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artificial aging time on torsional fatigue life and cyclic behavior of AA6351 aluminum alloy and evaluation of estimation methods

Abstract: The effects of artificial-aging time on monotonic properties and torsional fatigue of AA6351 aluminum alloy were studied in this paper. Fatigue tests were carried out by the strain-controlled condition. Monotonic and cyclic torsional behavior, fatigue life, and estimation methods were verified. Results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Therefore, 6xxx-series wall aluminum alloy also adopts the same failure system; (2) A large number of literature references [24][25][26]. Maurício et al [11] studied AA6351 aluminum alloy and found that the fatigue strength of AA6351 aluminum alloy reaches its peak at 170 • C and an aging time of 6 h. Iswanto et al [27] artificially aged A350a aluminum alloy for 2 h at 175 • C and 205 • C, respectively. The results showed that artificial aging treatment at 175 • C can improve the fatigue life and performance of aluminum alloys.…”
Section: Materials Selection and Preparation Process Of Thin-walled P...mentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, 6xxx-series wall aluminum alloy also adopts the same failure system; (2) A large number of literature references [24][25][26]. Maurício et al [11] studied AA6351 aluminum alloy and found that the fatigue strength of AA6351 aluminum alloy reaches its peak at 170 • C and an aging time of 6 h. Iswanto et al [27] artificially aged A350a aluminum alloy for 2 h at 175 • C and 205 • C, respectively. The results showed that artificial aging treatment at 175 • C can improve the fatigue life and performance of aluminum alloys.…”
Section: Materials Selection and Preparation Process Of Thin-walled P...mentioning
confidence: 99%
“…Therefore, it can be concluded that differences in the properties of the three profiles are independent of second-phase particles. Relevant literature shows that the β ′ ′ phase is the best particle for hindering dislocations in Al-Mg-Si alloys [11,26]. Among the three profiles, the 6xxx-2(1.33Mg/Si) profile has the highest total Mg + Si content.…”
Section: Second-phase Particle Precipitationmentioning
confidence: 99%
See 2 more Smart Citations
“…After the metal sheets are joined, multiple cycles (usually two to three) of heat treatment at nearly 200 • C are generally required for electrodeposition paint coating. This process, so called 'paint baking', introduces elevated temperatures similar to those used for the artificial aging of aluminum [8,9]. Therefore, the paint baking (PB) cycles can generate differences in the properties of the alloys from the as-received and welded mechanical properties of aluminum.…”
Section: Introductionmentioning
confidence: 99%